Pengamanan Tebing Pantai Tanjung Playu Batam - Nur Yuwono; Muhammad Effendi Saputra; Y Yuwono (Forum Teknik, 2003)
Tanjung  Playu  Beach, Batam  Island,  is  a wonderfull fishermen village.  The  housing  and public facilities are  built  a long  the  coast.  These  buildings and facilities are subject  to wave attack,  especially  during wave season  and  high tides.  In  order  to  combat  this  problem,  a special research  is  carried  out.This research  is  intended  to analyze the  problem  and  to find out  the solution  through  the  hydraulic  model  test.  Based  on this  research,  the  design  of sea wall is carried  out in  order  to  gct  a building which  environmentalyfriendly.Keywords:  wave attack,  hydraulic  model  test,  sea  wall.